Efektivitas Perda Kabupaten Sambas Nomor 11 Tahun 2015 tentang Bantuan Hukum bagi Masyarakat Miskin: Studi Sosio-Legal di Desa Pangkalan Kongsi - Serli Mardianti (CV Global Research Publication, 2025)
This study presents an in-depth, comprehensive, and critical analysis of the effectiveness of the implementation of Sambas Regency Regional Regulation Number 11 of 2015 concerning the Provision of Legal Aid in Pangkalan Kongsi Village, Tebas District. This research is motivated by the paradox between the normative guarantee of access to justice contained in regional regulations and the sociological reality of rural communities alienated from formal legal services due to structural, cultural, and geographical barriers. Using an empirical juridical approach (socio-legal research), this report dissects the interaction between legal substance, law enforcement structures, and the legal culture of the local community. The research findings reveal that although Sambas Regency has progressive legal instruments, their effectiveness in Pangkalan Kongsi Village is still low. This is caused by five main factors according to Soerjono Soekanto's theory of legal effectiveness: (1) The absence of technical regulations for the general public which contrasts with detailed regulations for ASN; (2) The limited reach of accredited Legal Aid Organizations (OBH) such as LBH Tridharma Indonesia due to operational constraints; (3) Severe physical infrastructure deficiencies, marked by damage to the main road in Muara Dungun Hamlet and the collapse of a vital suspension bridge, creating an unbearable cost barrier; (4) Low legal literacy among the poor, exacerbated by the stigma of legal fees; and (5) Strong cultural preferences for non-litigation dispute resolution through customary and deliberative mechanisms (Besaprah), which have not been optimally integrated with the state legal aid system. This report recommends budget policy reform, accelerated development of access infrastructure, and strengthening village-based paralegal schemes to bridge the justice gap.